Analisis Bentuk Bahasa Sindiran dalam Film Alangkah Lucunya Negeri Ini Karya Deddy Mizwar - Awalia Permata; Andi Tenri Sua; A. Nurhabibi Marwil (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study examines the form of satirical language found in the film Akan Lucunya Negeri Ini by Deddy Mizwar. The purpose of this study is to identify the forms of satirical language used in the film Akan Lucunya Negeri Ini. The research method used is qualitative descriptive. The research data was obtained from speeches that contained elements of satire spoken by the characters in the film Akan Lucunya Negeri Ini. The data collection process is carried out through documentation, listening, and recording techniques. Furthermore, the data is analyzed with data reduction stages to filter essential information, systematically present data, and draw conclusions based on existing findings. The results of the study show that the film Akankan Fununya Negeri Ini contains various forms of satirism. It was found that there were ironic satire characterized by subtle sarcasm, harsh cynicism with direct expressions and bitter words, sarcasm characterized by sharp and direct speech, satirical satire that criticized through humor, and innuendo sarcasm conveyed subtly and indirectly. These five forms of satire play an important role in conveying a deep social critique of the conditions of society and the system depicted in the film.